A causal layered analysis of movement, paralysis and liminality in the contested arena of indigenous mental health - Garvey, Darren Charles (Curtin University, 2015)
This qualitative investigation examined the social constructions of the Indigenous mental health arena with a view to understanding the tensions and conflicts experienced by providers and recipients of service within that site. A nuanced picture of the various movements of these players towards and away from the arena emerged, highlighting the navigation of paradox in unsettled contexts. The implications for intercultural competence are considered within a proposed notion of Cultural Agility.